Anti-wrinkle activity of the ethanol extract of Aronia melanocarpa for development of the cosmeceutical ingredients: Anti-wrinkle function of Aronia melanocarpa - Park, See-Hyoung (Cellular and Molecular Biology, 2024)
Despite the abundance of natural biological resources in Aronia melanocarpa, there is still insufficient research specifically exploring the potential for developing cosmeceutical compositions utilizing this plant. To develop the ingredient with the cosmeceutical function, the anti-wrinkle effect of the ethanol extract of A. melanocarpa was investigated. The ethanol extract was prepared from the dried A. melanocarpa. DPPH radical scavenging activity was significantly increased by the ethanol extract of A. melanocarpa. Cell viability on CCD986Sk human fibroblast was not affected by the ethanol extract of A. melanocarpa. Moreover, the ethanol extract of A. melanocarpa demonstrated inhibition of both collagenase and elastase enzymes. Analysis through ELISA and western blotting revealed an elevation in collagen expression levels in CCD986Sk human fibroblasts treated with ethanol extract. Additionally, the extract induced migration and invasion in HaCaT human keratinocytes, potentially associated with the activation of tight junctions. These results offer insights for the development of innovative cosmeceutical formulations utilizing A. melanocarpa extract.